A importância do estágio para a formação docente - Oliveira, Bruna de (Universidade Federal do Tocantins, 2021)
The present work aims to systematize the experience experienced in the Supervised Internship of the graduating class of 2017/1. I bring three monographs on Supervised Internship in the course of Pedagogy (undergraduate) of the University campus of Miracema / UFT: Jesus (2008) to contribute to my research; Silva (2009) and Neves (2011). I used in this teaching experience the qualitative research methodology and the structured interview as a data collection instrument. As a theoretical basis, I used Marconi & Lakatos (1986), Gerhardt & Silveira (2009) and Poupart (2008) who, besides guiding my exercise as a researcher, also contributed to my academic knowledge. Finally, my opinions on the Supervised Internship. The practical part of our course has many problems, but I can not fail to mention the enormous learning that we had during the internship, because teaching is a two-way, teaching and learning with my students at the same time.